Display of Organizational Commitment from State Civil Apparatus at the Secretariat of Regional Government of Kupang City, East Nusa Tenggara Province - Riwukore, Jefirstson Richset; Marnisah, Luis; Yustini, Tien; Habaora, Fellyanus (International Business Management - Universitas Ciputra, 2022)
The purpose of this research is to understand and determine of organizational commitment of the State Civil Apparatus at the Regional Government Secretariat of Kupang City, East Nusa Tenggara Province. This research has been conducted for 5 months, from January 2022 to May 2022 in Kupang City. The number of research respondents was 370 people who were determined by purposive stratified proportional sampling. The types of data used are primary and secondary data from interviews using a questionnaire, field observation, and documentation. The data analysis method used in this research is a descriptive analysis based on the average value of the Likert scale classification. The results showed that the component of organizational commitment in the high category was only a component of continuance commitment with an average value of 3.70, while those in the medium value category were affective commitment with an average score of 3.64 and normative commitment with an average value of 3.61. In general, the organizational commitment of the State Civil Apparatus in the Kupang City Government is still in the medium category with an average score of 3.65. This display of organizational commitment is likely to become a major obstacle to the performance of the state civil service. The strategy that can be carried out by local governments to increase organizational commitment is to increase the aspects of affective commitment and normative commitment of the State Civil Apparatus within the scope of the Regional Government Secretariat of the Kupang City. Keywords: organizational commitment, affective commitment, continuance commitment, normative commitment